Evaluasi Pelaksanaan Kegiatan Percepatan Penganekaragaman Konsumsi Pangan (P2KP) di Kota Makassar - Ida Rosada; N Nurliani; Chadrianah Dachlan Saleh (JURNAL GALUNG TROPIKA, 2021)
This study aimed to 1) evaluate the implementation of activities for the Acceleration of Food Consumption Diversification (P2KP) in Makassar City, 2). to analyzing the correlation between P2KP activities and the Expected Food Pattern (EFP) score in Makassar City, 3) analyzing/identifying changes in the quality of food consumption after participating in P2KP activities. The population in this study was the Women Farmers Group (WFG) beneficiaries of P2KP activities as many as 8 KWT in 8 sub-districts. Each sub-district has one WFG consisting of 30 households, so that the total population is 240 household. The sample was determined by Simple Random Sampling, namely 20% of the population, so there were 48 household. The results showed that the P2KP program in Makassar City with the success rate of program implementation included in the high category, namely 79.4%. There is a very significant relationship between P2KP activities and the Expected Food Pattern (EFP) score. There was a change in the quality of food consumption as reflected in the change in the Expected Food Pattern (EFP) score before and after P2KP activities. The higher the EFP score, the more diverse the food consumption.